Studies on functionalization of cellulose nanocrystals for development of polymeric Bionanocomposites and applications in sustainable chemical processes - Dhar, Prodyut (My University, 2017)
In recent decades, increased environmental concerns to reduce carbon foot print and rising prices of petrochemicals have attracted much attention towards developing green and sustainable biodegradable polymers and nanomaterials, which will help in securing the planet’s ecological balance. The studies based on utilization of renewable resources for development of value-added products ensuring environmental sustainability have become essential to confront the unprecedented implications of petroleum-based products related to global warming. Nature-based nanomaterials such as cellulose nanocrystals (CNCs), are derived from the abundantly available cellulosic biomass with unique inherent characteristics that have led to increased scientific and industrial attention. CNCs are the crystalline domain of cellulose with rod- like morphology and interesting properties such as high surface area, tunable aspect-ratio, chemical functionality, anisotropic mechanical properties, self-ordering behaviour to form optically active materials along with improved biocompatibility, biodegradability and non-toxic nature, provides it an upper hand in comparison to other nanoparticle derivatives. CNCs due to its sustainable nature, bio-origin and anisotropic mechanical behaviour have promising applications as reinforcing agents in polymeric nanocomposites, as targeted drug delivery vehicles, in biocatalysis, and in paper –based electronics as sensors.
Katiyar, Vimal
Kumar, Amit
Keywords: CHEMICAL ENGINEERING